MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KETERAMPILAN MEMBACA PEMAHAMAN MUATAN BAHASA INDONESIA MENGGUNAKAN MODEL BERGEMA SISWA KELAS V SEKOLAH DASAR - Jannah, Raudatul; Dwitalia Sari, Dessy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is the low critical thinking skills and reading comprehension skills in the Indonesian language content of fifth grade elementary school students. The solution to this problem is to use the BERGEMA model where this model is a combination of the Problem Based Learning, Student Teams Achievement Division, and Cooperative Integrated Reading and Composition learning models. The purpose of this study is to analyze students' critical thinking skills and reading comprehension skills. This study uses Classroom Action Research (CAR) which is carried out in four meetings. The subjects of this study are 19 fifth grade elementary school students. The results of this study indicate that students' critical thinking skills are implemented up to 85% with the criteria of very skilled and students' reading comprehension skills are implemented up to 89% with the criteria of very skilled.